Breastfeeding Practices and Immunity Outcomes among Infants: A Bibliometric Analysis 2012-2022 - Navya Tondak; Mahati Bhadania; Palka Mittal; Sapna Yadav; Aditya Kukreti; J. Swaminathan; Puneeta Ajmera (Journal of the Dow University of Health Sciences)
This study aimed to understand the significant relationships between human milk and a newborn's developing immune system over the decade as well as their history, research hotspots, frequency of publications, contextual associations between multiple publications related to the topic, and current trends. The electronic database TM Dimension AI was searched using the keywords “breastfeeding”, “immunity” and “infants” to include manuscripts published between 2012 and 2022. Bibliometric analysis was performed using VOSviewer 1.6.14. Network maps were created to analyze collaborations among distinct authors and countries, and recognize top institutions. The study covered 334 papers that meet the inclusion criteria. According to the network visualization, the United States has made a substantial contribution to the study of breastfeeding's effects on newborn immunity, as evidenced by the country's highest number of publications 74 (22.1%). The analysis of journals revealed the research in this area is heavily focused on Nutrient Journal, with maximum publications 104 (31.1%). On analyzing the contribution of institutes, the University of Western Australia showed a maximum publication 16 (4.7%). This bibliometric analysis highlights the United States as a leading contributor to research on breastfeeding's impact on infant immunity, with a significant focus on Nutrients journal and key institutional input from the University of Western Australia.